Питання історичної дидактики на сторінках "Українського історичного журналу" - Удод, О.А. (Український історичний журнал, 2017)
Окреслюється внесок «Українського історичного журналу» у становлення та розвиток історичної дидактики. Доводиться, що видання було і є трибуною для обговорення найактуальніших проблем дидактики та популяризації її досягнень. На сторінках часопису впродовж усієї його історії опубліковано лекції, консультації, методичні розробки з основних питань історичної науки, чим узагальнено кращий досвід викладання історичних дисциплін. The contribution of the “Ukrainian Historical Journal” to the formation and development of Ukrainian historical didactics is outlined in the article. In particular, it has been proved that the publication has always been and remains a platform for discussing the most urgent problems of didactics and popularizing its achievements. The best lectures, consultations, methodological developments of the main issues of historical science were published on the pages of the journal during its history. It summarizes the best practice of the teaching historical disciplines.